Freshwater on the international agenda - emergence of a regime complex - Werner, Andreas Frank (2015)
In the 21st century, water scarcity due to pollution, increasing demand and mismanagement has become a global phenomenon of growing concern. Often depicted in media reports, endorsed by global summits - such as the recent \"Rio+20\" Conference in 2012 in Brazil - and campaigned for by NGOs all over the world, freshwater issues play an important role within bigger debates on global environmental issues. Despite a clear increase in the intensity and scope of these issues over the last decades, they are not novel as such and have a history. This Ph.D. thesis analyzes the emergence and evolution of the freshwater topic on the international agenda since the early 1970s, when the first international freshwater-related conferences and conventions took place. In order to explain this genesis and evolution, the freshwater topic is situated within the broader international environmental agenda and is connected with International Relations scholarship on agenda-setting as well as international regimes. Subsequently, the empirical freshwater conventions and conference data is analyzed through these theoretical lenses, showing that the freshwater issue is in fact an umbrella topic which can be further subdivided into smaller water-related topics. The treatment of these sub-topics has led to conventions in two cases (wetlands and international watercourses) which are taken to be regimes in their own right, whereas others have so far remained limited to international conferences and events (sanitation, access to potable water etc.). Rather than seeing these as unconnected, individual regimes and conferences as has been done within contemporary scholarship, it will be argued that these in fact represent sub-regimes and parts of a bigger freshwater regime complex. Moreover, it will be argued that the origins of this regime complex are not due to specific countries´ deliberate aims of constructing international institutional overlap to subsequently explore forum-shopping opportunities to their advantage but, rather, that developments in this issue-area unintentionally resulted in this overlap for functional reasons.